Endurance sports events in Hungary in 2018-2019 - Maklári, Gergely (Acta Carolus Robertus, 2022)
Abstract In the course of the following study, I examine the popularity of endurance sports events held in Hungary in 2018 and 2019 based on secondary statistical data, and I analyse the role and importance of leisure sports, and present the situation and economic effects of endurance sports events. The results of the research confirm that, based on both 2018 and 2019 data, running races are the most popular of all competitions involving endurance sports. Triathlon and duathlon competitions are seasonally organised, with the vast majority of these events being held from May to September. The most common competitions in bicycle racing are in May, June and September. Most of the running events are held in September, but the months of April and May are also popular. The role of these events in tourism is also decisive, as it shows an increase in tourism consumption associated with various running events, due to the increase in the number of domestic and foreign participants entering competitions. In 2018, more than three times as many foreign runners participated in major Budapest competitions than 10 years earlier. The number of guest nights spent in Hungary increased roughly four times compared to 2007, and the spending generated by running tourism also increased more than six times (Hecker, 2019).